Impact of PLAI conferences, etc. to the professional development of librarians and information professionals, 1991-1995 - Villanueva, Aloha Ortega 1941-
A Likert-type questionnaire was administered to 200 librarians and information professionals from all over the country who were members of the PLAI from 1991 to 1995. Out of 85 accomplished questionnaires returned, only 72 were considered. Eight were disregarded due to non-attendance at any six conferences and five due to inconsistent answers. Percentages, modes, and means were used to analyze the data received.